Long-term age-dependent failure pattern after breast-conserving therapy or mastectomy among Danish lymph-node-negative breast cancer patients. Issue 1 (July 2016) - Laurberg, Tinne; Lyngholm, Christina Daugaard; Christiansen, Peer; Alsner, Jan; Overgaard, Jens
Abstract: Purpose: To describe long-term failure pattern after early-stage breast cancer in relation to local treatment (breast-conserving therapy (BCT) or mastectomy) and age. Materials and methods: Cohort study with balanced 5-year age groups and prospectively collected data; 813 Danish lymph-node-negative breast cancer patients diagnosed in 1989–98 and treated with mastectomy ( N = 515) or BCT ( N = 298) and no adjuvant systemic treatment. Results: The 20-year local recurrence (LR) risk was 20% after BCT; 8.7% after mastectomy. LR developed in mastectomy patients within the first 10 years; in BCT patients throughout the entire 20-year period. Younger patients' (⩽45 years) 20-year LR risk was generally higher than older patients' (>45 years) (19% vs. 5%, p < 0.001). In younger patients, LR was significantly associated with distant metastasis (DM) (hazard ratio (HR) = 2.7(1.8–4.2)) and 20-year breast-cancer mortality (HR = 2.7(1.7–4.4)). BCT was associated with higher 20-year breast-cancer mortality (HR = 1.5(1.0–2.4)) and higher 20-year all-cause mortality (HR = 1.7(1.2–2.5)) than mastectomy. In older patients, LR was not associated with DM, and breast-cancer mortality was similar for BCT and mastectomy. Conclusion: BCT patients with no adjuvant systemic treatment developed LR throughout 20-year period and faced higher LR risk than mastectomy patients. LR was associated with DM among younger patients, and younger BCT patients had higher mortality than younger mastectomy patients.